Teachers’ perceptions on the importance of occupational readiness skills for students with intellectual disabilities: a Japanese special education context - Maebara, Kazuaki; Yamaguchi, Asuka (Frontiers in Education, 2025)
In recent years, Japan has made significant progress in transitioning people with disabilities to competitive employment. This is because of employment quota systems and the increasing importance of special education schools in supporting the transition of persons with disabilities into society. This study demonstrated the importance of special education teachers’ skills in fostering occupational readiness. An online survey was conducted with 129 teachers from 10 special education schools in rural Japan to assess the importance of the 25 occupational readiness skills. The results showed that the teachers recognized the importance of occupational readiness skills during and after graduation. However, a significant difference was observed in the average importance scores of these skills. The teachers acknowledged the importance of adaptability to specific jobs as a crucial aspect of after-graduate support. These results highlight the difference between the emphasis on vocational education in special needs education in Japan and that perceived by vocational rehabilitation practitioners. Moreover, the survey revealed a strong recognition of the need for support in daily life and health management beyond graduation. This study highlights the importance of teaching specific skills in special education schools in Japan after graduation. Improving the educational content and strengthening collaboration with vocational rehabilitation institutions is necessary to enhance transition support.